Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1210/jc.2015-1530
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-193b Controls Adiponectin Production in Human White Adipose Tissue

Abstract: In human adipocytes, miR-193b controls adiponectin production via pathways involving nuclear transcription factor Yα and possibly nuclear receptor interacting protein 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 19 publications
0
42
1
Order By: Relevance
“…Nine of these miRNAs significantly reduced the secretion of pro-inflammatory chemokine (C–C motif) ligand 2 (CCL2), which was in line with the observation that they were downregulated in AT in human obesity (Arner et al, 2012). More-over three of these downregulated miRNAs were recently found to increase ApN secretion in conditioned media (Belarbi et al, 2015). The previous study of Ge et al also identified that miR-883b-5p, which was upregulated by ApN and downregulated in omental AT of obese human repressed the lipopolysaccharide-binding protein (LBP) and TLR4 signaling (Ge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nine of these miRNAs significantly reduced the secretion of pro-inflammatory chemokine (C–C motif) ligand 2 (CCL2), which was in line with the observation that they were downregulated in AT in human obesity (Arner et al, 2012). More-over three of these downregulated miRNAs were recently found to increase ApN secretion in conditioned media (Belarbi et al, 2015). The previous study of Ge et al also identified that miR-883b-5p, which was upregulated by ApN and downregulated in omental AT of obese human repressed the lipopolysaccharide-binding protein (LBP) and TLR4 signaling (Ge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As for the human WAT, numerous miRs exist but only a few number is altered in obesity and type 2 diabetes mellitus such as miR-193b, whose expression correlates positively with adiponectin gene expression and negatively with homeostasis model assessment of insulin-resistance [26].…”
Section: Introductionmentioning
confidence: 99%
“…Further, overexpression of miR-378 in 3T3L1 cells decreased mRNA and protein levels of adiponectin (Ishida et al 2014). A similar study in humans have shown significant association of serum adiponectin level with increased expression of miR-193b in white adipose tissue (Belarbi et al 2015). Few studies have implicated miRNA in degradation of adiponectin receptor.…”
Section: Introductionmentioning
confidence: 98%
“…The potential role of miRNA in insulin resistance (IR) and type 2 diabetes has been explored although there is potential for further investigation. Few recent studies indicate their potential as diagnostic and prognosis biomarkers (Ling et al 2012, Chakraborty et al 2014, Belarbi et al 2015, Chuang et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation